Comparative study of microfinance sustainability: Credit risk-taking and capital structure - Marwa Fersi; Mouna Boujelbène Abbes (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
The purpose of this paper was to investigate the determinants of risk-taking in the context of Islamic and conventional microfinance institutions (MFIs) while considering the capital structure's role in moderating the risk-taking decisions' effect on financial performance. Fixed and Random effects GLS with a first-order autoregressive disturbance was used to empirically analyze the impact of risk-taking on performance as well as the role of capital structure in moderating the effects on the relationship between non-performing loans and performance. The dataset covers 179 Conventional MFIs and 57 Islamic MFIs in four different regions over the 2005-2015 period. Risk-taking determinants exposed by high loan growth, low-interest margin, and low loan loss provisions were revealed to have negative consequences on risk exposures for both MFIs on average. These indicators are significantly and positively related to a lower loan portfolio quality. Therefore, this risk-taking behavior harms these MFIs' performance. The moderating effect of capital structure within leverage funding on the relationship between non-performing loan indicators and financial performance was confirmed in Conventional microfinance institutions. This paper can be considered a pioneer attempt to evaluate the determinants of risk-taking decisions and their implications on the financial performance and sustainability of microfinance institutions.
Keywords: G21; G23; G41; 330; Credit risk taking; capital structure; non-performing loans; performance; microfinance institutions